Potential solutions to problems posed by the offspring sex ratios of people with parasitic and viral infections - James, William H (Folia parasitologica, 2010)
I have hypothesized that mammalian offspring sex ratios (proportions male at birth) are partially controlled by the hormone levels of both parents around the time of conception. Recently data have been published (privately) which impugn suggestions of mine (based on that hypothesis) relating to the offspring sex ratios of people who are carriers of hepatitis B virus; and (publicly) to hormone profiles of women who are infected with the protozoan parasite Toxoplasma gondii. Here these data are reviewed in the light of data on offspring sex ratios of people infected with hepatitis C, and cytomegalovirus and T. gondii; and of mice with T. gondii and the trichostrongyline nematode Heligmosomoides polygyrus. Three proposals are made viz: 1. Women infected with T. gondii may have high oestrogen levels. This would potentially explain reports of their high offspring sex ratios, long gestations and (perhaps) behavioural traits. 2. Some of these infective organisms may 'prefer' a particular endocrine environment in their host (in the sense that it facilitates replication or transmission or both). 3. Some of these organisms apparently cause changes in that endocrine environment as a consequence of their presence. If both the latter two proposals were correct, it could explain recent puzzling data on the offspring sex ratios of hepatitis B carriers. And if this solution turns out to be correct, it would suggest new endocrine means of combating hepatitis B infection.
Keywords: virové nemoci; Male; Female; Humans; Mice; poměr pohlaví; Parasitic Diseases; Sex Ratio; ženské pohlaví; Hormones; Virus Diseases; lidé; parazitární nemoci; hormony; mužské pohlaví; Animals; zvířata; myši